The Unorthodox Theory of Forms in Plato's Philebus - James Wood (Revista de Filosofia Antiga, 2017)
This paper argues that we can make best sense of four key passages as well as the Philebus as a whole by rejecting the “orthodox” view that forms exist separately from particulars as determinate entities in their own right and accepting the “unorthodox” view that forms exist within particulars as their limiting and unifying measures and the ousiai of their geneseis.